Chirality control of inorganic materials and metals by peptides or amino acids. Issue 4 (27th May 2020) - Kim, Hyeohn; Im, Sang Won; Kim, Ryeong Myeong; Cho, Nam Heon; Lee, Hye-Eun; Ahn, Hyo-Yong; Nam, Ki Tae
Abstract : In this review, we exploit recent investigations to identify the exceptional roles of amino acids and peptides in chirality, based on local atomic conformation to macroscopic chiral morphology. Abstract : Chirality exists everywhere in nature and may be one of the most important features in biological systems. The chirality of amino acid molecules is transferred to the peptide sequences, determining the secondary and further three-dimensional structures. As a result, even the macroscopic chirality observed in many living features can be controlled by the peptide sequence. Interestingly, recent studies have shown that achiral inorganic materials and metals, according to the crystallographic point group, can develop chiral morphologies that are precisely controlled by the amino acids and peptides. As a result, strong chiral optical responses can be generated even at visible wavelengths. In this review, we have highlighted recent pioneering examples to show the enantioselective interactions between inorganic materials/metals and amino acids/peptides and discussed the underlying mechanisms.